PARENTS' OBLIGATIONS ON HADHANAH BEFORE MUMAYYIZ AFTER DIVORCE: REVIEW OF NORMATIVE LEGAL STUDIES - Asman, Asman (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2022)
This study examines the law of neglect and neglect of children by parents, this problem often occurs in society, on the other hand, fighting for children between divorced parents often occurs as if children are property that can be divided and after being divided, the bond is broken parents who do not get custody. The problem of raising children in Islamic Jurisprudence (fiqh) terms is called hadhanah, which is defined as caring for small children who do not know and cannot live independently, namely by fulfilling their needs. In relation to the custody of minors as a result of the divorce of both parents given to the mother, this is as regulated in Article 105 of the Compilation of Islamic Law. However, although Article 105 of the Compilation of Islamic Law explains that a child who has not mumayyiz is the right of the mother, it does not mean that the father has no right in the child's growth and development. This research method uses a qualitative research type, while the approach in this research uses two approaches, namely: the statutory approach and the fact approach. The results of this study are the responsibility of parents to minors in providing a living for their children after divorce according to Islamic law becomes the obligation of male parents, this is as regulated in Article 49 letter d and Article 156 of the Compilation of Islamic Law.